2021
DOI: 10.3390/cells10082114
|View full text |Cite
|
Sign up to set email alerts
|

Selective Autophagy in Hyperglycemia-Induced Microvascular and Macrovascular Diseases

Abstract: Dysregulation of autophagy is an important underlying cause in the onset and progression of many metabolic diseases, including diabetes. Studies in animal models and humans show that impairment in the removal and the recycling of organelles, in particular, contributes to cellular damage, functional failure, and the onset of metabolic diseases. Interestingly, in certain contexts, inhibition of autophagy can be protective. While the inability to upregulate autophagy can play a critical role in the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 110 publications
(113 reference statements)
0
17
0
Order By: Relevance
“…Autophagy plays a vital role in the development of various cardiovascular diseases (42). It has been reported that miR-34a suppresses autophagy in cancer cells (43).…”
Section: Mir-34a and Autophagy In The Cardiovascular Systemmentioning
confidence: 99%
“…Autophagy plays a vital role in the development of various cardiovascular diseases (42). It has been reported that miR-34a suppresses autophagy in cancer cells (43).…”
Section: Mir-34a and Autophagy In The Cardiovascular Systemmentioning
confidence: 99%
“…In addition, Parkin dysfunction may lead to the loss of pancreatic β cells and the development of insulin deficiency [105]. Bharath and colleagues found that in diabetic mice, the level of p53 increased in β-cells, inhibiting Parkin-mediated mitophagy [106]. However, in p53 deficient mice, restored mitophagy protected β-cell loss induced by streptozotocin (STZ).…”
Section: Mitophagymentioning
confidence: 99%
“…Autophagy is an important pathway for recycling through lysosomal removal of misfolded proteins, damaged organelles, etc ( Bravo-San Pedro et al, 2017 ). Mitochondrial autophagy is specific macroautophagy that selectively degrades damaged or senescent mitochondria for recycling and is susceptible to the intracellular environment ( Bharath et al, 2021 ; Chen et al, 2022b ). In AMPK knockout mouse embryonic fibroblasts, ULK1 is not activated, autophagy is inhibited and damaged mitochondria accumulate.…”
Section: Ampk Signalling Pathwaymentioning
confidence: 99%